Meningkatkan Kemampuan Motorik Kasar Anak Tunagrahita Sedang Melalui Lempar Tangkap Bola - Wardani, Dedi Nurdiana Kusuma; Sopandi, Asep Ahmad (Jurnal Penelitian Pendidikan Khusus, 2022)
This study aims to prove whether the game of throwing and catchingthe ball can improve the gross motor skills of mentally retardedchildren. The research method used is classroom action researchwhich consists of two cycles. With the game of throwing and catchingthe ball, the gross motor skills of mentally retarded students canincrease. Based on the results of the study, gross motor skills at thebeginning increased compared to before using the ball throwing game.This can be seen from the results of research using the game ofthrowing and catching the ball to improve gross motor skills.